The Density and Sex Ratio of Cockle Shell (Anadara granosa) in Coastal Water of Panipahan, Pasir Limau Kapas District - Hadi Sastranegara; Efriyeldi '; Yusni Ikhwan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
A study on the density, sex ratio of cockles (A. granosa) was conducted in Panipahan coastal mud-flat during May to August 2015. Two zones of 100 m and 250 m from coast line were established. Each sampling zone were divided into 5 plots of 1 m2. Apparently average density of cockles ranged from 25.9 - 28.4 ind/m2. There was no significant differently of cockles density between zones (p>0.05). Sex-ratio male/female appeared 1:1.27.Keyword : Density, Sex Ratio, Anadara granosa and Panipahan